Analysis of Factors Affecting Carbon Emissions in Indonesia - Tirtana, Dodi; Nurlailatin, Indah; Salsabilla, Febyyola (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2023)
This research aims to examine the variables affecting Indonesia's carbon emissions between 2000 and 2022, with particular emphasis on the consumption of renewable energy sources, coal and oil. Indonesia is the object of this research, and data information is collected from official sources of the World Bank and Our World in Data. The amount of renewable energy, coal, and oil consumed is the independent variable, while carbon emissions are the dependent variable. The research method involves time-series multiple linear regression analysis with statistical testing steps to identify the causal relationship between variables. EViews software was used for statistical testing. Findings show a significant correlation between Indonesia's carbon emissions and the consumption of renewable energy, coal and oil. Strategies to expand the use of renewable energy to reduce carbon emissions are the main focus of the policy implications. This research provides a foundation for sustainable policy development to address Indonesia's carbon emission problem. Pro-renewable and anti-fossil policy recommendations need to be considered to achieve the sustainable goal of reducing carbon emissions and dealing with climate change in Indonesia.